Supporting the Accounting, Management Systems, and Entrepreneurship of Milk Pie Production Businesses as Contributors to the Tourism Industry in Bali - Ni Wayan Sitiari; Ni Nyoman Rusmiati; Ni Nengah Seri Ekayani (Asian Journal of Community Services, 2023)
Bali's tourism growth is closely tied to the local culinary scene, especially the famed milk pie. To bolster Bali's status as a tourist hub, businesses must adopt digital accounting and marketing systems. Unfortunately, many entrepreneurs lack a solid grasp of accounting and have yet to embrace digital marketing. This community service project aims to enhance the partners' abilities in financial planning through proper accounting, boost entrepreneurial intentions, and improve digital marketing skills. Methods include discourse and assistance on accounting system, digital marketing strategies, and entrepreneurial skills. The results show that partners increase entrepreneurial enthusiasm and improve record-keeping according to accounting standards. Ultimately, this should boost milk pie sales, enhance product quality, and benefit for entrepreneurs in Denpasar.